International capital flows to Latin America - Griffith-Jones, Stephany (ECLAC SantiagoCL, 2000)
Looks at the general pattern of financial flows to Latin America over the last three decades and how the recent trend in flows fits into that overall picture of high volatility. Examines the links between capital flows and growth. Focuses on each major category of flows - foreign direct invetment, portfolio flows and bank lending - examining the trends of the flows and the terms and conditions on which they enter the region. Concludes with some policy recommendations.